Decoding Creativity in the Digital Age: Blockchain Unveiled - Navigating Opportunities and Challenges in Copyright Protection - Disemadi, Hari Sutra; Girsang, Junimart; Selina, Selina (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The advent of blockchain technology is heralded as a promising solution to address the challenges associated with digital copyright. Nevertheless, given the nascent stage of blockchain development, there exist a number of formidable challenges that necessitate resolution.Purposes of the Research: This study endeavors to analyze the opportunities and challenges associated with the implementation of blockchain technology in safeguarding digital copyright.Methods of the Research: This study employs the normative legal research method with a qualitative approach. The utilization of a qualitative approach in normative legal research allows for a nuanced exploration of legal principles and norms. Results of the Research: The findings of the research underscore that blockchain technology, characterized by features such as decentralization, security, transparency, and immutability of data, presents opportunities for enhancing information transparency, detecting fraudulent claims, safeguarding the digital music industry, and automating license payments through smart contracts. Nevertheless, challenges must be addressed before blockchain can be widely implemented, including regulatory uncertainties and cybersecurity threats. Collaboration among government entities, academia, industry players, the private sector, and regulatory authorities is imperative to establish a clear and secure legal framework for the adoption of blockchain technology.